Bullying Prevention Strategies through the Foster Guardian Program in Pesantren - Zahid, Reza Ahmad (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
Amid growing concerns over bullying in educational environments, Islamic boarding schools have initiated foster guardian programs as a preventive measure, aiming to create a safer and more nurturing atmosphere for their students. This approach seeks to leverage these institutions' communal and familial structures, promoting a culture of care and respect among students. This study aims to reveal bullying prevention strategies through foster guardian programs in Islamic boarding schools. The research method in this study employs a qualitative case study approach. The results of this study have two main findings. First, the foster guardian program results from an initiative by the boarding school administrators. The program has been operational from 2016 to the present. The inception and sustainability of the program are based on the evaluation and reflection of the boarding school administrators on the various challenges they face in caring for junior students. The concept of foster guardians is also a result of adapting the concept of parenting within a family, such that foster guardians assume the role of older siblings to their younger counterparts. Second, foster guardians creatively prevent and address bullying problems among students. This creativity is characterized by various forms of foster guardian efforts dubbed bullying prevention strategies, which include identifying the root of the problem, fostering an attitude of mutual love and affection, providing advice and punishment, and increasing room-based activities. This study suggests that addressing bullying in Islamic boarding schools involves parenting strategies that incorporate anti-bullying awareness, Islamic teachings, school traditions, and psychology.